The Use Of Translators At Local Municipalities: A Case Study Of Moqhaka Local Municipality, South Africa - Hlohlolo, Sephiri David (Central Univeristy of Technology, 2018)
Local municipalities in South Africa are seen as the first phase of government, because they are nearer to the citizens. The functions of local municipalities are to provide service delivery to residents within their municipal jurisdiction. This study is intended to highlight the fact that language services are to be taken as service delivery issues and be implemented by local municipalities as prescribed in the Constitution of the Republic of South Africa (Act. No 108 of 1996). The Bill of Rights as enshrined in the Constitution of the Republic of South Africa (Act. No 108 of 1996) stipulates that the communities have a right to maintain their linguistic and cultural activities within their municipal jurisdiction. This study used the critical theory to determine the contextual factors that appear to help in understanding the language rights of Black literate and semi-literate residents within local municipalities in South Africa. This study employed mixed methods approach. Open-ended interviews were conducted with Moqhaka Local Municipality officials. A questionnaire was completed by Black literate and semi-literate residents within the Moqhaka Local Municipality. Qualitative data was analysed using interpretative-phenomenological data analysis while quantitative data was analysed using Statistical Package for Social Sciences. The results from both qualitative and quantitative data revealed that the use of translator(s) is a need and essential in helping out (better understanding of municipal language of choice) Black literate and semi-literate residents within the Moqhaka Local Municipality. Both the Moqhaka Local Municipality officials and Black literate and semi-literate residents were aware of the value of using translator(s) and started seeing them (translators) as the vehicle for the promotion of their indigenous African languages and multilingualism. Translator(s) are valuable in ensuring that residents within local municipalities in South Africa are afforded their language rights to be accommodated in their preferred languages, taking into cognisance the official municipal language, as per Municipal Systems Act. No 32 of 2000. Local municipalities have language policies which in turn have provided for the employment and use of translator(s). As a result, an effective language policy should be triumphed by the implementation plan and employment of translator(s) thereof. It is pivotal to establish a language unit at local municipalities in South Africa in order to promote indigenous African languages and multilingualism. There cannot be an effective language policy without a language practitioner (for this study translator or translators). It appears as if there is no political will or commitment to promote indigenous African languages at some local municipalities in South Africa. This is because of ten (10) sampled local municipalities in the Free State, of only two (2) have full-time employed translators. Local municipalities have raised a concern that languages are an unfunded mandate; as a result there is no mention of language practitioners (for this study translator or translators) in the Integrated Development Plan (IDP) or within municipal organograms. Local municipalities will be advised and encouraged to have language services within their Integrated Development Plan (IDP) to address the stipulation of the Constitution of the Republic of South Africa (Act. No 108 of 1996). The study recommends that local municipalities (for this study, Moqhaka Local Municipality) respond to the stipulations in the Constitution of the Republic of South Africa (Act. No 108 of 1996) and use translator(s) when communicating with residents (especially Black literate and semi-literate).
Thesis
Keywords: Translators; Constitution of the Republic of South Africa (Act. No 108 of 1996); Indigenous African languages; Multilingualism; Bill of Rights; Implementation; Integrated Development Plan (IDP)